INFLUENCE OF CHEMICALLY ACTIVE COMPONENTS OF THE ENVIRONMENT IN THE CONTACT RESISTANCE AND CORROSION RESISTANCE OF CONTACT MATERIALS - Korobskyy, V. (Energy and Automation, 2016)
Estimated transfer resistance and corrosion resistance of the materials in the electric-reactive Sereda change mass and contact resistance. It is found that the gaseous medium significantly affects the properties robochem contact surfaces due to the formation on the surface of products of primary and secondary chemical reactions. Displaying high corrosion resistance developed contact materials in gaseous environments.